The Concept of Legality and Morality Regarding Marriage Polygamy from Sharia Perspective and Human Rights - Sa'adah, Nurul Karomatus (Maliki Interdisciplinary Journal, 2024)
Polygamy is a family issue that is still being debated both theologically and anthropocentrically. Basically, the permissibility of polygamy has been discussed explicitly in Islamic law and positive law. However, in its application among the community, discussions regarding polygamy have not yet found a bright spot. As the times progressed, polygamy became a normal thing to do without considering the elements of cause and effect. Therefore, writing this article is intended to provide an in-depth understanding regarding the legality of polygamy in Indonesia and the moral elements contained in polygamy, so whether it is still relevant or not.